PEDAGOGICAL ROLE OF ACMEOLOGY IN THE SYSTEM OF SOCIAL SCIENCE AND PERSONALITY AWARENESS - Abdurakhimov Shogosim Abdurakhmonovich (Journals Park Publishing, 2023)
In this article, in order to study "Acme"-forms as a reason for the development of optimal technologies for the development of successful and creative professional skills and professional skills, a comprehensive study of the processes and methods implemented by various specialists of acmeology professional activity is carried out. Acmeology follows step by step the mechanisms and results of macro, meso, microenvironments (state, society with education and labor principles, family, etc.) and external conditions.
Keywords: Acmeology, professional, macro, meso, microenvironments, laws, technology.